The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1111/j.1540-8159.1998.tb01101.x
|View full text |Cite
|
Sign up to set email alerts
|

What Range of Programmable AV Delays is Necessary in Antibradycardia DDD Stimulation?

Abstract: DDD pacemakers differ considerably in device specific extents of AV delay (AVD) programmability. To demonstrate the requirements of a mean DDD pacemaker patient population optimal AVDs in 200 DDD pacemaker patients (age 8 to 91 years) were estimated by left atrial electrography. The results should help to define an AVD programmability standard. Left atrial electrograms were recorded via a bipolar filtered esophageal lead. The method aims on adjusting the left atrial electrogram to 70 ms prior to the ventricula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Autocapture: On PV delay: 120 ms, AV delay: 190 ms (in agreement with suggestions from the literature) 8,9 Negative AV/PV Hysteresis Search: Off Rest Rate: Off Rate Adaptive PV delay: Off AICS: randomized to On or Off according to the randomization list. Other parameters: up to the investigators.…”
Section: Study Proceduressupporting
confidence: 83%
“…Autocapture: On PV delay: 120 ms, AV delay: 190 ms (in agreement with suggestions from the literature) 8,9 Negative AV/PV Hysteresis Search: Off Rest Rate: Off Rate Adaptive PV delay: Off AICS: randomized to On or Off according to the randomization list. Other parameters: up to the investigators.…”
Section: Study Proceduressupporting
confidence: 83%
“…Next, constant AP with an AV delay of 70 msec was programmed and complete preexcitation achieved. In healthy adults, AP and AS have the same hemodynamic effect when the difference in the corresponding AV delays is about 30 msec [4,7]. Concerning the electromechanical effect, in our patient AP was superior to AS when the difference in the AV delays was 30 msec.…”
Section: Discussionmentioning
confidence: 56%
“…Kindermann [10] considers AV opt = 88 ms ± 35 ms with atrial triggering, and AV opt = 143 ms ± 41 ms for the AV sequential mode. Knorre [18] has determined AV opt = 100.5 ± 27.8 ms for atrial triggering, and AV opt = 169 ± 24.5 ms for the AV sequential mode. Haskel [5] has established the best AV interval to be 150 ms. Janosik [6] considers AV opt = 144 ± 48 ms with atrial triggering, and AV opt = 176 ± 44 ms for the AV sequential mode.…”
Section: Discussionmentioning
confidence: 99%
“…Leman et al [16] have demonstrated that it is also possible to utilize measurement of left ventricular ejection fraction and stroke volume by myocardial thallium scintigraphy as a means of AV interval optimization. A further possibility involves detection of left atrial depolarization by an esophageal electrode recording [17,18]. During recent years, the use of Doppler echocardiography in conjunction with the mitral valve inflow profile has been investigated as means of AV interval optimization: i.e., Ritter's method [19].…”
Section: Introductionmentioning
confidence: 99%